(E)-1-(2,4-Dinitrophenyl)-2-(3-ethoxy-4-hydroxybenzylidene)hydrazine - Fun, Hoong Kun; Chantrapromma, Suchada; Ruanwas, S Pumsak; Kobkeatthawin, Thawanrat; Chidan Kumar, C. S. (International Union of Crystallography, 2014)
The molecule of the title hydrazine derivative, C15H14N4O6, is essentially planar, the dihedral angle between the substituted benzene rings being 2.25 (9). The ethoxy and hydroxy groups are almost coplanar with their bound benzene ring [r.m.s. deviation = 0.0153 (2) A ° for the ten non-H atoms]. Intramolecular N—H O and O—H Oethoxy hydrogen bonds generate S(6) and S(5) ring motifs, respectively. In the crystal, molecules are linked by O—H Onitro hydrogen bonds into chains propagating in [010]. Weak aromatic – interactions, with centroid–centroid distances of 3.8192 (19) and 4.0491 (19) A ° , are also observed.